2019
DOI: 10.1021/jacs.9b08578
|View full text |Cite
|
Sign up to set email alerts
|

A Bulky Chiral N-Heterocyclic Carbene Palladium Catalyst Enables Highly Enantioselective Suzuki–Miyaura Cross-Coupling Reactions for the Synthesis of Biaryl Atropisomers

Abstract: Axially chiral biaryl scaffolds are essential structural units in chemistry. The asymmetric Pd-catalyzed Suzuki–Miyaura cross-coupling reaction has been widely recognized as one of the most practical methods for constructing atropisomers of biaryls. However, longstanding challenges remain in this field. For example, substrate scope is often narrow and specialized, functional groups and heterocycles can lead to reduced reactivity and selectivity, bulky ortho-substituents are usually needed, and reported methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(88 citation statements)
references
References 101 publications
0
81
0
Order By: Relevance
“…Although some advances have been achieved using phosphine ligands, their tedious synthesis and, in some cases, intrinsic ease of oxidation excludes practical applications on a large scale. In contrast, the rigid structure of NHCs (N-heterocyclic carbenes) provides an excellent opportunity to form stable gold complexes with a well-defined chiral environment, as was proven in the case of other metals, such as palladium [26][27][28][29], ruthenium [30][31][32][33] or copper [34][35][36][37][38][39][40][41][42]. Moreover, adequately planned structure of NHC ligands allows for tuning of their electronic and steric properties, which is not easily achievable in the case of phosphines [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Although some advances have been achieved using phosphine ligands, their tedious synthesis and, in some cases, intrinsic ease of oxidation excludes practical applications on a large scale. In contrast, the rigid structure of NHCs (N-heterocyclic carbenes) provides an excellent opportunity to form stable gold complexes with a well-defined chiral environment, as was proven in the case of other metals, such as palladium [26][27][28][29], ruthenium [30][31][32][33] or copper [34][35][36][37][38][39][40][41][42]. Moreover, adequately planned structure of NHC ligands allows for tuning of their electronic and steric properties, which is not easily achievable in the case of phosphines [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the axial chirality has been found in a variety of rotation-hindered molecules [32][33][34][35][36][37][38][39] , such as BINAP and BINOL derivatives, which have been widely used as privileged ligands or catalysts in asymmetric catalysis [40][41][42][43][44][45] . Inspired by the unique structures of these chiral ligands with axial chirality, we…”
mentioning
confidence: 99%
“…In 2019, Shi and co-workers described the first highly enantioselective N-heterocyclic carbene (NHC)-Pd-catalyzed Suzuki-Miyaura cross-coupling reaction for the synthesis of atropisomeric biaryls. [13] Av ariety of axially chiral biaryls, heterobiaryls,a nd tetra-ortho-substituted biaryls were efficiently prepared in high yields with excellent levels of enantiocontrol from readily available substrates.T hese reactions tolerate aw ide scope of heterocycles and functional groups,employ low catalyst loading, and proceed under mild conditions.I na ddition to this broad substrate scope,t he authors also demonstrated the possible access to ternaphthalenes 5a,b via ad ouble Suzuki-Miyaura cross-coupling between dibromonaphthalene 3 and naphthylboronic acid 8 (Scheme 4). Key to the success of the reaction was the development and application of the very bulky C 2 -symmetric chiral NHC ligand L2 for the Pd catalyst.…”
Section: Aryl-aryl Cross-coupling (Type Dmolecules)mentioning
confidence: 99%